Commuting time as a barrier to urban accessibility in the São Paulo Metropolitan Region (SPMR), Brazil - Silva, Ricardo Barbosa da (Geografares, 2024)
This paper aims to analyze the role of commuting time in public transport for urban accessibility to employment rates in the São Paulo Metropolitan Region (SPMR), over the last three decades. The methodology used combines quantitative and qualitative approaches. The quantitative approach was based on the use of microdata from the São Paulo Metro Origin and Destination (OD) survey, for the years 1997, 2007 and 2017, to analyze the cumulative accessibility to jobs, as a function of travel time by collective mode in the MRSP. For the qualitative approach, collaborative mapping workshops on accessibility were held with University in Unified Educational Centers (UniCEU)/Open University System of Brazil (UAB) participants from Perus, Capão Redondo and Água Azul – Cidade Tiradentes centers. Commuting time was found to be a barrier to urban accessibility to jobs, especially for poor residents of the urban peripheries in the SPMR.
Keywords: urban accessibility; commuting time; barriers